Student Voices on Digital Pedagogy: A Case Study of Zoom-Based TOEFL Preparation for Non-English Department Students - Tristiana, Novita Eka; Episiasi, Episiasi; Seftika, Seftika (Edukasi, 2026)
The increasing reliance on synchronous video-conferencing platforms in post-pandemic higher education has transformed the delivery of high-stakes language preparation programs, including TOEFL courses. While previous studies have largely focused on test score improvement and general online learning implementation, limited research has explored students’ reflective experiences in Zoom-mediated TOEFL preparation contexts. This qualitative case study investigates non-English department students’ feedback and reflections on the use of Zoom in a TOEFL preparation program at a private university in Indonesia. Data were collected through reflective journals and semi-structured interviews and analyzed using thematic analysis. The findings reveal two overarching themes. First, students perceive Zoom as facilitating learning effectiveness, flexibility, and real-time interaction, which support their understanding of TOEFL materials and test-taking strategies. Second, although the platform enhances motivation and accessibility, technical constraints such as unstable internet connections and reduced face-to-face interaction remain challenges. By foregrounding student voice, this study contributes nuanced insights into how synchronous digital pedagogy shapes learners’ experiences in test-oriented language instruction. The findings offer pedagogical implications for instructors and institutions seeking to optimize Zoom-based TOEFL preparation programs while addressing technological and interactional limitations.